2018
DOI: 10.1002/jcp.26764
|View full text |Cite
|
Sign up to set email alerts
|

The competing endogenous circular RNA ADAMTS14 suppressed hepatocellular carcinoma progression through regulating microRNA‐572/regulator of calcineurin 1

Abstract: Emerging evidence have discovered that circular RNAs (circRNAs) may serve as diagnostic or tumor promising biomarkers. This study aimed to investigate how circular RNA ADAMTS14 (circADAMTS14) regulates microRNA‐572/ regulator of calcineurin 1(miR‐572/ RCAN1) in hepatocellular carcinoma (HCC). The expression profiles of circRNA/microRNA (mRNA) between HCC tissues and paired adjacent tissues were analyzed via microarray analysis. The expressions of circADAMTS14, miR‐572, and RCAN1 were measured by real‐time pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
(48 reference statements)
3
28
0
Order By: Relevance
“…SP1-related transcriptional regulation of ADAMTS3 gene expression in osteosarcoma cell models [54]. Furthermore, the competing endogenous circular ADAMTS14 might suppress HCC progression through regulating miR-572/RCAN1 as the competing endogenous RNA [55]. Nonetheless, to the best of our knowledge, this is the first study to investigate the role of ADAMTS14 protein expression in OSCC and also the first study to investigate the association between ADAMTS14 protein expression and other clinicopathological features of OSCC.…”
Section: Discussionmentioning
confidence: 89%
“…SP1-related transcriptional regulation of ADAMTS3 gene expression in osteosarcoma cell models [54]. Furthermore, the competing endogenous circular ADAMTS14 might suppress HCC progression through regulating miR-572/RCAN1 as the competing endogenous RNA [55]. Nonetheless, to the best of our knowledge, this is the first study to investigate the role of ADAMTS14 protein expression in OSCC and also the first study to investigate the association between ADAMTS14 protein expression and other clinicopathological features of OSCC.…”
Section: Discussionmentioning
confidence: 89%
“…CircADAMTS14, which is downregulated in the HCC cell line, acts as a sponge of miR‐572 to regulate the expression of RCAN1 and thereby inhibit HCC progression . It has also been found that circADAMTS13 acts as a tumor suppressor during HCC progression through a functional pathway as a miR‐484 sponge .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…Recent evidences have suggested that circRNAs involve in far‐ranging biological processes, including transcription, mRNA splicing, RNA decay and translation, and their deregulation takes pivotal roles in the development and metastasis of various tumors, such as glioma, 15 hepatoblastoma, 16 colorectal cancer, 17 lung cancer, 18 prostate cancer, 19 bladder cancer, 20 and gastric cancer 21 . For example, Li et al revealed that circANKS1B promotes colorectal cancer cell migration and invasion by working as a molecular sponge of miR‐149 to regulate FOXM1 and Slug protein expressions 17 .…”
Section: Introductionmentioning
confidence: 99%